Terrestrial Fern Diversity in Palak Siring Waterfall and Its Potential to Support Junior High School Science learning - Maharani Husnul Khotimah; M. Sutarno; Deni Parlidungan; Mellyta Uliyandari; Aprina Defianti (Postgraduate, University of Mataram, 2023)
The Palak Siring Waterfall is a natural tourism object located in Kemumu Village, Armajaya District, North Bengkulu Regency were the area have variety of vegetation. This research aims to analyze the Terrestrial Fern Diversity in that area. The benefits of ferns in an ecosystem are as one of the pioneer organisms that open and start a new life in an ecosystem, food sources, and planting media. The method used is transect by forming (five) plots based on the slope of the land, consist of flat, sloping, rather steep, steep, and very steep areas. Plot size of 20 x 20 m placed along the transect line. Based on the survey was found 22 species with 13 types of family ferns in the Palak Siring Waterfall. The Diversity Index value of ferns (pteridophyta) belongs to the medium category. This certainly indicates that there is a fern that can adapt to the environment as well as other plants in area. Diversity of fern have the potential to be applied to junior high school science learning through several Basic competencies, materials, and forms of learning activities.